Knowledge translation - Bratianu, Constantin; Garcia-Perez, Alexeis; Dal Mas, Francesca; Bedford, Denise (Working methods for knowledge management., 2024)
Knowledge translation is a topic that originated in the field of health sciences where the need to move research to practice is of critical importance. In parallel, the field of knowledge sciences has developed a research base around knowledge transfer, knowledge sharing, knowledge exchange, knowledge articulation and knowledge absorption. This book brings these two important tracks together and synthesizes the fragmented literatures. It also draws from essential work on human communication and considers how these concepts are affected by the knowledge economy. The book raises awareness of the critical role that knowledge translation plays in every academic field of study, and in everyday life. To demonstrate this role, the book presents a grounding model that readers can use to better 'see'their knowledge translation challenges and opportunities. Drawing on the author team's experience in a range of domains and sectors, the book explores knowledge translation in the fields of manufacturing, infectious diseases, automated call centers, regulatory development and compliance, financial lending, transportation safety, and doctor-patient discourse.